Isolated renal metastasis from squamous cell lung cancer - Cai, Jun; Liang, Gai; Cai, Zhiqiang; Yang, Ting; Li, Shuang; Yang, Jiyuan (Multidisciplinary Respiratory Medicine, 2013)
Renal metastasis from non-small cell lung cancer is rather uncommon. The mechanism underlying the occurrence of metastasis in this site is still not well understood. We report a case of a 53-year-old Chinese woman who had moderately differentiated squamous cell carcinoma of the lung. After a ten months post-surgery interval of disease free survival, computed tomography (CT) scan found that left renal parenchymal was occupied by a mass, confirmed by kidney biopsy to be a metastasis from squamous cell lung carcinoma. Based on this case, we are warned to be cautious in diagnosis and treatment when renal lesion are detected.